At home and in the field : ethnographic encounters in Asia and the Pacific islands. - Pigliasco, Guido Carlo; Pigliasco, Guido Carlo; Finney, Suzanne S.; Finney, Suzanne S.; Mostafanezhad, Mary; Young, Forrest Wade; Mostafanezhad, Mary (University of Hawaiʻi Press, 2015)
Crossing disciplinary boundaries, 'At Home and in the Field' is an anthology of twenty-first century ethnographic research and writing about the global worlds of home and disjuncture in Asia and the Pacific Islands. These stories reveal novel insights into the serendipitous nature of fieldwork.
Bibliographic Level Mode of Issuance: Monograph.
Keywords: Ethnology -- Fieldwork -- Asia.; Ethnology -- Fieldwork -- Oceania.; Ethnologie -- Recherche sur le terrain -- Asie.; Ethnologie -- Recherche sur le terrain -- Océanie.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Anthropology -- General.; Ethnology -- Fieldwork; Asia; Oceania; Anthropology.; Social & Cultural Anthropology.; Social Sciences.